2011
DOI: 10.1007/s00253-011-3609-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel probiotic delivery system based on microencapsulation with protectants

Abstract: The establishment of the health-promoting benefits of probiotics is challenged by the antimicrobial bio-barriers throughout the host's gastrointestinal (GI) tract after oral administration. Although microencapsulation has been frequently utilised to enhance the delivery of probiotics, microcapsules of sub-100 μm were found to be ineffective and therefore questioned as an effective delivery vehicle for viable probiotics despite the sensory advantage. In this study, four probiotics strains were encapsulated in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 35 publications
3
18
0
7
Order By: Relevance
“…Our study showed that the presence of sucrose coincided with the significantly enhanced preservation of favorable physiological conditions among all the six strains. It agreed with the reports about the supportive role of metabolizable sugars for the acid tolerance of bacteria (Chen et al 2012;Corcoran et al 2005). The protection is fulfilled by energizing the membrane-bound F 1 F 0 -ATPase proton pump (Chen et al 2012;Lorca and Font de Valdez 2001), which consequently maintains a near-neutral cytoplasmic pH for bacteria.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our study showed that the presence of sucrose coincided with the significantly enhanced preservation of favorable physiological conditions among all the six strains. It agreed with the reports about the supportive role of metabolizable sugars for the acid tolerance of bacteria (Chen et al 2012;Corcoran et al 2005). The protection is fulfilled by energizing the membrane-bound F 1 F 0 -ATPase proton pump (Chen et al 2012;Lorca and Font de Valdez 2001), which consequently maintains a near-neutral cytoplasmic pH for bacteria.…”
Section: Discussionsupporting
confidence: 85%
“…It agreed with the reports about the supportive role of metabolizable sugars for the acid tolerance of bacteria (Chen et al 2012;Corcoran et al 2005). The protection is fulfilled by energizing the membrane-bound F 1 F 0 -ATPase proton pump (Chen et al 2012;Lorca and Font de Valdez 2001), which consequently maintains a near-neutral cytoplasmic pH for bacteria. Because the esterase activity of LAB strains was commonly found to be optimal at pH 6 to 7 and severely inhibited below pH 4 (Choi and Lee 2001;Gobbetti et al 1997;Wang et al 2004), the normal functionality of intracellular enzymes as revealed by cF staining may have provided evidence for the undisturbed internal pH under the stress of acidity.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This is in accordance with the definition given by Food and Agriculture Association of the United Nations (FAO) and World Health Organization (WHO) which probiotic bacteria can be define as "live microorganisms that when consumed in adequate amount can give beneficial effects to the host health" [2,3] . However, there are difficulties in maintaining the viability of the probiotic cells during processing, storage and exposure along the gastrointestinal tract due to highly acidic condition in the stomach, bile acid elements in intestinal fluids and some others [4].…”
Section: Introductionmentioning
confidence: 99%